Growth and Pb Uptake of Brassica campestris Enhanced by Two Ecological Earthworm Species in Relation to Soil Physicochemical Properties - Tibihenda, Cevin; Zhang, Menghao; Zhong, Hesen; Xiao, Ling; Wu, Ling; Dai, Jun; Liu, Kexue; Zhang, Chi (Frontiers in Environmental Science, 2022)
A comprehensive understanding of the influence of earthworms on the growth and Pb accumulation of leafy vegetables is significant for soil management and human health. This study was aimed to evaluate the different influences of two ecological earthworm species on the growth and Pb accumulation of Brassica campestris in a Pb-contaminated soil and their relationship with soil physico-chemical properties. In a 30-day microcosm experiment, the anecic and native earthworm species Amynthas aspergillum and the epigeic species Eisenia fetida were inoculated in soil artificially contaminated with Pb at different levels (i.e., 0, 100, 500, and 1,000 mg kg−1), and B. campestris was grown. With a survival rate of 81%–100%, A. aspergillum was more tolerant to Pb contamination than E. fetida with 46%–84%. At the same time, earthworm inoculation significantly increased soil Pb bioavailability (p < 0.05). At the 500 and 1,000 mg kg−1 Pb levels, the treatments with earthworm inoculation showed higher plant biomass, leaf area, and chlorophyll concentration than the treatments without earthworm. The principal component analysis (PCA) showed that earthworm inoculation exerted a stronger effect on soil properties than Pb contamination, but the latter had a stronger effect on plant growth and Pb accumulation. Compared with A. aspergillum, E. fetida had a greater effect on soil cation exchange capacity, available Pb, and plant growth and Pb accumulation. In contrast, A. aspergillum had a greater effect on soil C and N contents than E. fetida. The co-inertia analysis revealed that plant Pb accumulation was positively correlated with soil available Pb and CEC. The leaf chlorophyll concentration was closely related to soil Eh, pH, and Dissolved organic carbon. The findings of this study showed that in the Pb-contaminated soils, earthworm inoculation exerted a strong effect on soil physicochemical properties and the growth and Pb accumulation of the leafy vegetable B. campestris. Both the epigeic earthworm species E. fetida and the anecic species A. aspergillum were associated with higher Pb accumulation or concentration in B. campestris, which may bring a possible risk to food security.